SELECTION PARAMETERS THROUGH ASSESSMENT OF INTERRELATIONSHIP AND PATH ANALYSIS BETWEEN YIELD AND YIELD COMPONENTS IN SUMMER MAIZE (ZEA MAYS L.) - VASI ANNI MANOHARI; MARKER , SHAILESH; THIYAGARAJAN, NIRUPAMA (The Bioscan, 2018)
The aim of the study was to estimate correlation and path analysis, from which desirable characters could assist the plant breeder in ascertaining criteria to be used for the breeding programmes. Thirty three genotypes were evaluated at Field Experimentation Center, Department of Genetics and Plant Breeding, Naini Agricultural Institute, Sam Higginbottom University of Agriculture, Technology and Sciences during Zaid, 2017. From the present work, grains per row (0.20*), 100 seed weight (0.91**) and cob length (0.39**) at genotypic level were found to be responsible for positive and strong association on grain yield. Path analysis also revealed largest direct effects through grains per row (0.10), 100 seed weight (0.85) and cob length (0.16) at genotypic level on grain yield and hence indirect selection for yield based on these characters would be appreciable.